Molecular mechanism of human anti-Zika non-structural protein 1 antibodies - Ho, Jun Sheng (Nanyang Technological University, 2022)
Zika virus (ZIKV) is an arthropod-transmitted flavivirus that has seen significant outbreaks globally, with the potential to cause neurological or birth abnormalities. There remains a large unmet need for efficacious vaccines and antivirals against ZIKV. Recently, four monoclonal antibodies (mAbs) from an infected patient were found to bind to ZIKV non-structural protein 1 (ZvNS1) and engage Fcγ-receptors without inducing antibody-dependent enhancement in vitro. While these mAbs were found to be non-neutralizing, one was protective in a mouse challenge model. Here, we sought to solve the complex formation of ZvNS1, with full-length (FL) and Fab fragments of human AA12, EB9, and GB5 antibodies to understand the mAb-NS1 interactions and expedite development of anti-NS1 antibodies in diagnostics and therapeutics. We confirmed that ZvNS1-FL mAbs is co-eluted and stable, and that mammalian expression systems were suitable for producing ZvNS1 and FL mAbs with high yield. An anti-Fab nanobody (AFNb) to aid complex visualisation appears to bind both GB5 and AA12 Fab with low affinity. Challenges faced in the ZvNS1-Fab complexation suggest that the Fc region influences binding affinity of overall mAb. Further investigation to elucidate the binding epitopes is expected to unravel new insights into the use of mAbs for anti-ZvNS1 applications.